Answer:
Kevin can make 35 pillows.
Step-by-step explanation:
I assume that your question would be, "How many pillows can Kevin make?" If this is not the answer that you were looking for, you need to input your question.
Answer:
( x+1)^2 + (y+2)^2 = 25
The center is (-1, -2) and the radius is 5
Step-by-step explanation:
x^2 + 2x + y^2 + 4y = 20
Complete the square
2/2 =1 1^2 =1 so add 1 for x 4/2 =2 2^2 = 4 so add 4 for y
x^2 +2x +1 +y^2 +4y+4 = 20 +1 +4
( x+1)^2 + (y+2)^2 = 25
(x+1) ^2 + (y+2)^2 = 5^2
(x - -1) ^2 + (y - -2)^2 = 5^2
This is in (x-h)^2 + (y-k)^2 = r^2 form where (h,k) is the center and r is the radius
The center is (-1, -2) and the radius is 5
Answer:
the m angle ABC is 19x+12
Answer:
The second term of the sequence is 8 False ⇒ B
The third term of the sequence is 3 True ⇒ A
The fourth term of the sequence is -3 True ⇒ A
Step-by-step explanation:
The form of the recursive rule is:
f(1) = first term; f(n) = f(n - 1) + d, where
- f(n - 1) is the term before the nth term
- d is the common difference
∵ f(1) = 15, f(n) = f(n - 1) - 6 for n ≥ 2
∴ The first term = 15
∴ d = -6
let us find the 2nd, 3rd, and 4th terms
∵ n = 2
∴ f(2) = f(1) - 6
∵ f(1) = 15
∴ f(2) = 15 - 6 = 9
∴ The second term is 9
∴ The second term of the sequence is 8 False
∵ n = 3
∴ f(3) = f(2) - 6
∵ f(2) = 9
∴ f(3) = 9 - 6 = 3
∴ The third term is 3
∴ The third term of the sequence is 3 True
∵ n = 4
∴ f(4) = f(3) - 6
∵ f(3) = 3
∴ f(4) = 3 - 6 = -3
∴ The fourth term is -3
∴ The fourth term of the sequence is -3 True
Answer:
-2/1
Step-by-step explanation:
i hope this helps :)